Comparison of the effect of repeated-sprint training combined with two different methods of strength training on young soccer players - Campos-Vazquez, M. A.; Boza, S. R.; Toscano-Bendala, F. J.; Leon-Prados, J. A.; Suarez-Arrones, L.; Gonzalez-Jurado, J. A. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to assess the effect of combining repeated-sprint training with 2 different methods of muscle strength training on physical performance variables in young players. Twenty-one soccer players with mean (±SD) age of 18.1 (±0.8) years, weight 69.9 (±6.5) kg, and height 177.1 (±5.7) cm, and competing in U-19 category, were randomly assigned to 2 experimental groups: squat group (SG: n = 10) and take-off group (TG: n = 11). Intervention in both groups consisted of the combination of a weekly session of repeated-sprint training (the same for both groups), with 2 weekly sessions of strength training (different for each group), for 8 weeks in the final period of the season. The strength sessions for the SG consisted of conducting a series of full squats executed at maximum velocity in the concentric phase. Intervention in the TG was the performance of 2 specific strength exercises (take-offs and change of direction), with measurements taken before and after consideration of the following variables: repeated-sprint ability (RSA), yo-yo intermittent recovery test level 1 (YYIRT1), countermovement jump (CMJ), and average velocity in full squat progressive loads test. The SG improved CMJ height in 5.28% (p = 0.05) and FS37.5-47.5-67.5 (p = 0.05), whereas the TG improved FS17.5-27.5-37.5-47.5-67.5 (p = 0.05). There were no significant changes in the values of RSA or YYIRT1 in either group. The results seem to show that the combination of a weekly session of repeated-sprint training with 2 weekly sessions of strength training could be an insufficient stimulus to improve RSA in the final period of the season.